The Effectiveness Of Sabo Dam Modular As A Clean Water Intake Weir (Case Study Of Work For Huntap Tondo Raw Water Project) In Palu City, Central Sulawesi - Prasetyo, Eko; Yulianti, Erni; Dewi, Grace Citra (Journal Research of Social Science, Economics, and Management, 2023)
This research discusses the topography and geology of Palu City, Central Sulawesi, as well as the condition of the land around the "Works for Huntap Tondo Raw Water" project. The research results show that environmental factors, topography, geology, and soil conditions influence project planning and implementation. Therefore, a deep understanding of these factors is essential in ensuring the success and sustainability of the project. This research shows that the planning and implementation of the "Works for Huntap Tondo Raw Water" project in Palu City, Central Sulawesi, must pay attention to diverse geographical and geological conditions, soil conditions, and environmental factors in ensuring the success and sustainability of the project. Apart from that, the use of Modular Sabo Dam technology as a clean water intake weir is also an efficient and effective solution in managing the water supply in this project. The involvement of local residents also needs to be considered in project implementation to ensure success and support the surrounding environment. Key words: topography, geology, soil conditions, Sabo Modular Dam, Huntap Tondo Raw Water, local residents.